دراسة مخبرية لاختبار ثبات الدعامات في أنظمة الزرع التي تعتمد مبدأ ( TIF ) لربط الدعامات بالغرسات - عيسى, نزيه; بهرلي, ناصر; حسنه, رانيا اسماعيل (Latakia University Journal -Medical Sciences Series, 2019)
تهدف هذه الدراسة إلى تقييم ثبات الدعامات على الغرسات في أنظمة الزرع (TIF) Tapered Interference Fit التي تعتمد مبدأ الاحتكاك بدلا من براغي التثبيت لربط الدعامات بالغرسات كما هو الحال في نظام بايكون Bicon system for implantology . أجري هذا البحث على عشرين غرسة مع دعاماتها. بقياسات وأبعاد موحدة من نظام Bicon. حيث تم تثبيت الدعامات على الغرسات الموافقة بحسب تعليمات الشركة المنتجة بتطبيق طرقة واحدة وطرقتين وثلاث وأربع طرقات, ثم تم اختبار ثبات الدعامات باستخدام آلة شد نوع INSTRON . وأظهرت النتائج أن تطبيق ثلاث طرقات يحقق التثبيت الأفضل و أن زيادة عدد الطرقات لم يحقق تثبيت أفضل بشكل مهم . حيث تبين بتطبيق تحليل التباين ANOVA بين المجموعات الأربع أن هناك فروقاً جوهرية في معدل التثبيت فيما بينها حيث(0.05 > 0.000 p= ). كذلك وجد من خلال تطبيق اختبار أقل فرق معنوي LSD لإجراء مقارنة تفصيلية بين المتغيرات الأربع أنه لا يوجد فرق جوهري في قوة التثبيت بين المجموعتين (3 و4) حيث أن (0.05< 0.131 p=)بينما يوجد فرق جوهري بين أي من المجموعتين السابقتين مع المجموعتين (1و2). وهذا يدل على ضرورة استخدام الطريقة المتبعة مع إحدى المجموعتين (3 أو 4) . This study aims to evaluate the stability of the Abutment-Implants Connection in the Tapered Interference Fit implant systems (TIF) that depend on the friction concept for retention instead of the abutment screws to connect the abutments to the implants as is the case in Bicon system for implantology. With unified measures and dimensions from Bicon system twenty implants were used with its abutments, where the abutments were fixed to its implants according to the instructions and guidance from the manufacturer by applying one, two, three and four beats, the fixity has been then tested using a general tensile machine type INSTRON. The results show that the application of three beats gives the optimal fixation. This result means that the increasing of the beat’s number didn’t apparently give better fixation. ANOVA analysis shows that there are significant differences in the fixation rate between the four groups as the result was (p=0.000<0.05). Also found through the application of the Least Significant Difference test LSD which gives a detailed comparison between the four variables that there is no essential difference between the third and the fourth groups (p=0.131<0.05. This indicates that we need to use the technique which used with the third or fourth group for fixing the abutments to the implants.